(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Hospital is one of the high-risk workplaces in terms of safety and health. Nurses are the most vulnerable health workers to work accidents because they have the most number in a hospital and most often interact with patients. Safety performance is very important for the prevention of work accidents. This research aimed to analyze the influence of safety management practices on safety performance in nurses of the emergency installation at X Hospital of Surabaya. Methods: This research was an observational research with the cross-sectional design. It was conducted in May to June 2019. The population in this study was 208 nurses and the sample obtained using a simple random sampling technique involving 68 nurses. In assessing safety management practices and safety performance, the researcher used questionnaires, observation, and interviews. Results: The results presented that safety training which was a dimension of safety management practices affected on the safety performance with a p-value 0.000. Suggestions in this research, to improve safety performance, management can conduct specific and periodic safety training, holding safety briefing and safety talk on a regular basis, and implementing a safety award by applying a system of reward and punishment. Conclusion: Hospital management still needs to schedule a specific and periodic safety training for nurses. Furthermore, to improve safety performance, management can holding safety briefing and safety talk on a regular